2013
DOI: 10.1016/j.jep.2013.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of seselin from Clausena anisata (Rutaceae) leaves and its effects on the feeding and development of Lucilia cuprina larvae may explain its use in ethnoveterinary medicine

Abstract: Ethnopharmacological relevance: The leaves of Clausena anisata are used traditionally to expel maggots from wounds of animals in Zimbabwe. We have previously proved in the laboratory that the plant certainly affects the behaviour and growth of blowfly larvae. The objective of this study was to isolate and identify the active compounds responsible for this activity. Materials and Methods:The acetone extract of C. anisata leaf powder was separated by solvent-solvent partition into five fractions. The n-hexane fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
0
34
1
1
Order By: Relevance
“…Although seselin, a pyranocoumarin previously isolated from C. anisata (Mukandiwa et al, 2013), had larvicidal activity against A. aegypti larvae in our previous studies (Mukandiwa et al, 2015); in this study it was not repellent, and it appears that the adulticidal activity observed for the extracts cannot be attributed to seselin. Attempts at isolating a single active component from the plant was not successful as repellency activity decreased as the extract was sequentially separated through fractionation.…”
Section: Space Spraying Assaycontrasting
confidence: 58%
See 3 more Smart Citations
“…Although seselin, a pyranocoumarin previously isolated from C. anisata (Mukandiwa et al, 2013), had larvicidal activity against A. aegypti larvae in our previous studies (Mukandiwa et al, 2015); in this study it was not repellent, and it appears that the adulticidal activity observed for the extracts cannot be attributed to seselin. Attempts at isolating a single active component from the plant was not successful as repellency activity decreased as the extract was sequentially separated through fractionation.…”
Section: Space Spraying Assaycontrasting
confidence: 58%
“…In Cameroon it is used as an insecticide against stored-grain pests. The insecticidal and repellent activities against stored grain pests and feedingdeterrence activity against blowfly larvae have been confirmed in scientific studies (Boeke et al 2004;Ndomo et al 2008;Mukandiwa et al 2013). In Kenya and Ethiopia, the leaves of C.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Daunnya mengandung minyak atsiri yang berbau seperti minyak anis. Kandungan bioaktif seselin di dalam daun Klausena efektif mengendalikan larva lalat Lucina cuprina (Mukandiwa et al 2013 Penggunaan pestisida sintetis yang terus menerus dapat menimbulkan beberapa masalah diantaranya terjadinya resurjensi, resistensi serta ledakan hama dan patogen kedua, pencemaran lingkungan baik pada litosfer, hidrosfer maupun atmosfer (Solichah et al 2004). Kebanyakan dari pestisida sintetis tidak dapat larut sempurna dalam air, akibatnya residu pestisida tersebut akan meningkat lewat rantai makanan sehingga dapat membahayakan manusia karena senyawanya ada yang bersifat karsinogen.…”
Section: Pendahuluanunclassified